PENGARUH SISTEM INFORMASI AKUNTANSI PENJUALAN TERHADAP EFEKTIVITAS PENGENDALIAN PIUTANG PADA PT. SHIBA AZAKI - Haryo kusumo; Febryantahanuji Febryantahanuji (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
The purpose of this study was to test the effectiveness of the accounting information system at PT. SHIBA AZAKI. The problem in this study is whether this sales information system has an effect on controlling receivables at PT. SHIBA AZAKI. In this study the author uses quantitative research methods, while the type of associative research uses a questionnaire as an instrument used to obtain data. The population used in this study were all employees of PT. SHIBA AZAKI using 36 people as research samples. The result of this research is that there is a positive influence and significant of the sales accounting information system on the effectiveness of controlling accounts receivable at PT. SHIBA AZAKI